Study on xLiVPO4F·yLi3V2(PO4)3/C Composite for High-Performance Cathode Material for Lithium-Ion Batteries - Zhong, Shengkui; Zhang, Xiaoping; Liu, Jiequn; Sui, Yulei (Frontiers in Chemistry, 2020)
Cathode materials of xLiVPO4F•yLi3V2(PO4)3/C (x:y=1:0, 2:1, 0:1) are synthesized via a feasible sol-gel method for high performance lithium ion batteries. The structures, morphology and electrochemical properties of the composites are thoroughly investigated. The results show that LiVPO4F/C, Li3V2(PO4)3/C and 2LiVPO4F•Li3V2(PO4)3/C can be synthesized under 750 °C without the formation of impurity. Meanwhile, the unique morphology of the 2LiVPO4F•Li3V2(PO4)3/C composite, which is porous with nanoflakes adhered to the surface, is revealed. This composite integrates the advantages of LiVPO4F and Li3V2(PO4)3. There are four discharge plateaus near 4.2, 4.1, 3.7 and 3.6 V, and the cathode material delivers high capacities of 143.4, 141.6, 133.2, 124.1 and 117.6 mAh g-1 at 0.1, 0.2, 0.5, 1 and 2 C rates, respectively. More importantly, the discharge capacity can be almost fully recovered when the discharge rate returns to 0.1 C. The study is highly promising for the development of cathode material for LIBs.